Earle H. Kincaid papers - Kincaid, Earle H. (Earle Hill), 1894-
Correspondence and other records pertaining to Kincaid's career as an officer in the U.S. Navy. Documents his tours of duty with the Asiatic Fleet in China and the Philippines in the 1930s; at the U.S. Naval Training Station in Newport, R.I., in the early 1940s; and in Oceania in World War II. Also includes material pertaining to his work in meteorology in the 1920s.
U.S. naval officer. Died 1961.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Naval Training Station (Newport, R.I.); United States. -- Navy -- Foreign service -- China; United States. -- Navy -- Foreign service -- Oceania; United States. -- Navy -- Foreign service -- Philippines; United States. -- Navy. -- Asiatic Fleet; Meteorology; World War, 1939-1945 -- Oceania; Naval officers